1983
DOI: 10.1111/j.1365-2125.1983.tb01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of blood pressure to continuous heavy coffee drinking in young volunteers. A double‐blind crossover study.

Abstract: 1 In a double-blind crossover trial, the effect of 4 week daily ingestion of eight cups of regular coffee (corresponding to 504 mg caffeine) vs eight cups of decaffeinated coffee was studied. Blood pressure, heart rate and urinary catecholamines were measured in eight healthy, young volunteers. 2 In both groups, regular coffee immediately led to a significant increase in mean blood pressure (+ 3 and + 5 mm Hg respectively). The difference between both groups, however, existed only in the first 3 to 5 days of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
3

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 13 publications
2
33
1
3
Order By: Relevance
“…The effects of repeated caffeine intake have also been studied in controlled studies using continuous ambulatory monitoring to measure blood pressure (Table 4). Some of the long-term studies have shown that caffeine induced persistent pressor effects (by 3 ± 6 mmHg) in habitual consumers (Ammon et al, 1983;Burr et al, 1989;James, 1994;Rakic et al, 1999). Changing from caffeinated to decaffeinated coffee (van Dusseldorp et al, 1989;Superko et al, 1994) or abstinence from coffee (Bak & Grobbee, 1990;Superko et al, 1994) resulted in a slight fall (by 2 ± 5 mmHg) in blood pressure.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…The effects of repeated caffeine intake have also been studied in controlled studies using continuous ambulatory monitoring to measure blood pressure (Table 4). Some of the long-term studies have shown that caffeine induced persistent pressor effects (by 3 ± 6 mmHg) in habitual consumers (Ammon et al, 1983;Burr et al, 1989;James, 1994;Rakic et al, 1999). Changing from caffeinated to decaffeinated coffee (van Dusseldorp et al, 1989;Superko et al, 1994) or abstinence from coffee (Bak & Grobbee, 1990;Superko et al, 1994) resulted in a slight fall (by 2 ± 5 mmHg) in blood pressure.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
“…The pressor response has been reported as diminishing within a few days of the start of regular intake of caffeine (Robertson et al, 1981(Robertson et al, , 1984Ammon et al, 1983;Myers & Reeves, 1991). However, the tolerance may be partial, because in some studies caffeine was still able to elevate blood pressure during habitual consumption (Burr et al, 1989;Jeong & Dimsdale 1990;James 1994;Green & Suls, 1996).…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine is often regarded as a cardiovascular risk factor; however, there is conflicting epidemiological evidence on the relation of caffeine consumption to the occurrence of acute cardiovascular events (6)(7)(8)(9)(10)(11)(12)(13). The conflicting evidence may in part be due to the various pleiotropic effects caffeine has on cells at physiologically achievable concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…A switch to caffeine produced a small increase in blood pressure during the first few days, with levels falling and returning to baseline thereafter. We did not observe a transient rise in blood pressure, possibly because we measured blood pressure weekly, whereas Ammon et al 7 took blood pressure measurements every day. Robertson and colleagues 18 -19 also observed complete tolerance to caffeine after 7 days of caffeine ingestion.…”
mentioning
confidence: 73%